KREATIVITAS SISWA DALAM PEMBUATAN ALAT MUSIK BOTOL KACA PADA PEMBELAJARAN NADA DI KELAS IV SD NEGERI SUNGAPAN - Rahma, Sofia; Melsya Fitrikasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of making glass bottle musical instruments in music education and to analyze the creativity and understanding of musical scales among fourth-grade elementary school students. The study employed a descriptive qualitative approach with fourth-grade students and one classroom teacher at Sungapan Public Elementary School as subjects. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that initial instruction tended to be teacher-centered and lacked the use of media, resulting in students being less active and experiencing difficulty understanding the concept of musical scales. The implementation of glass bottle musical instruments increased student engagement, creativity, and enthusiasm in learning. Students were able to explore sounds through variations in water volume, attempt to produce high and low pitches, and collaborate in playing simple musical instruments. Additionally, students became more confident and active during practical activities. The use of glass bottle musical instruments also helps students understand the concept of musical scales more concretely through direct experience. The conclusion of this study indicates that glass bottle musical instruments are effective as a creative, interactive, and student-centered alternative medium for music education. This study contributes to the development of music education media in elementary schools, though it is limited to the context and a specific number of subjects.